Prevalence of type 2 diabetes mellitus complications among adults (Herald of the National Children's Medical Center, 2024)
This article discusses the main risk factors for type 2 diabetes in adults and measures to eliminate them.Materials and methods of research: The clinic of the Republican Specialized Scientific and Practical Medical Center of Endocrinology named after Academician E.Kh. Turakulov conducted a study of complications among adult patients with type 2 diabetes.Results of the study: Type 2 diabetes among adults occurs with complications and there is an increase in obesity and concomitant diseases. Given the prevalence of complicated forms of the disease, it is necessary to develop a plan of preventive measures to solve the problem.Conclusion: Lifestyle changes, including healthy eating and physical activity, are key to managing type 2 diabetes and obesity. Early detection of complications and promoting a healthy lifestyle are the best strategies to prevent and manage type 2 diabetes in adults.
Keywords: diabetes mellitus type 2; obesity; body mass index; retinopathy; nephropathy; prevention